Confucianism ideology in educational policies of the Mac dynasty during ruling Thang Long (1527-1592) - Nguyễn, Thị Ngọc Thảo (2023)
The Mac dynasty began to rule the whole of Đai Viet around the end of the 15th century – at the beginning of the 16th century, when things began to fall apart as a severe economic crisis came around, severely affected the by-then dynasty of the Le, which was at that time, seriously degenerated: the mandarinate is alienated,life of most peasants became increasingly painful, thus justified the formation of the Mac dynasty. In just a short amount of time, they have managed to re-build the government apparatus, from central to local. Over 65 years ruling in Thang Long, the Mac dynasty have left their marks on all crucial fields including political, economics and culture, especially the strong attention was paid to the improvements of the education system. That was credited for the massive number of scholars serving for both the Mac dynasty and its later representatives. Based on inheriting data from previous researchers, the following paper describes in-depth about the Mac dynasty’s education system (1527 – 1592) and the remarkable feat it has brought.